Recent developments and current management of penile cancer. (March 2014) - Hadway, Paul; Sahdev, Varun; Arya, Manit; Muneer, Asif
Penile carcinoma is a rare disease, with over 95% of tumors being squamous cell carcinomas. Due to the low case numbers there has been a paucity of good-quality prospective studies available on which to base best clinical practice. The development of specialist high-volume centers in both the UK and Europe has started to permit multicenter collaboration and analysis of larger cohorts, with a knock-on improvement in patient care. Advances in diagnostic imaging, surgical techniques for both the penis and inguinal regions, and improved delivery of radiotherapy have helped to improve outcomes and quality of life. Molecular biology has started to shed light on the pathogenesis of the disease and the role that human papillomavirus may play. The aim of this article is to give an up-to-date review of the management of penile cancer encompassing the above.